2017
DOI: 10.1038/s41467-017-02084-0
|View full text |Cite
|
Sign up to set email alerts
|

The anthelmintic praziquantel is a human serotoninergic G-protein-coupled receptor ligand

Abstract: Schistosomiasis is a debilitating tropical disease caused by infection with parasitic blood flukes. Approximately 260 million people are infected worldwide, underscoring the clinical and socioeconomic impact of this chronic infection. Schistosomiasis is treated with the drug praziquantel (PZQ), which has proved the therapeutic mainstay for over three decades of clinical use. However, the molecular target(s) of PZQ remain undefined. Here we identify a molecular target for the antischistosomal eutomer — (R)-PZQ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
72
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(78 citation statements)
references
References 33 publications
6
72
0
Order By: Relevance
“…Chiral 1,2,3,4‐tetrahydroisoquinolines (THIQs) are widely distributed in various natural bioactive alkaloids and also serve as important intermediates in pharmaceutical chemistry . Compounds containing THIQ skeleton exhibit a variety of biological activities, such as antitumor, antimalarial, anthelmintic, antihypertensive, targeting of the central nervous system, and inhibiting Keap1‐Nrf2 protein‐protein interactions . Their biological activities are occasionally stereoselective in terms of their potency, metabolism and bitter taste …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chiral 1,2,3,4‐tetrahydroisoquinolines (THIQs) are widely distributed in various natural bioactive alkaloids and also serve as important intermediates in pharmaceutical chemistry . Compounds containing THIQ skeleton exhibit a variety of biological activities, such as antitumor, antimalarial, anthelmintic, antihypertensive, targeting of the central nervous system, and inhibiting Keap1‐Nrf2 protein‐protein interactions . Their biological activities are occasionally stereoselective in terms of their potency, metabolism and bitter taste …”
Section: Introductionmentioning
confidence: 99%
“…[7] Their biological activities are occasionally stereoselective in terms of their potency, metabolism and bitter taste. [4,8] Considerable effort has been devoted to the enantioselective preparation of chiral THIQs. Chemical asymmetric synthesis method are important and frequent sources of these compounds.…”
Section: Introductionmentioning
confidence: 99%
“…We further demonstrated this as supernatants of PZQ‐treated cells strongly suppressed proliferation of bystander T cells, and this was partly restored by blocking IL‐10. Interestingly, a recent study showed that PZQ acted as an agonist for the human serotonin receptor 5‐HT2BR, demonstrating its ability to modulate human cells . T cells express serotonin receptors upon their activation and it is theoretically possible that PZQ may utilize 5‐HT2BR to exert its action on human T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, a recent study identified a serotonin receptor as a cellular receptor for PZQ . PZQ bound specifically to the 5‐HT2BR and elicited contraction of mouse mesenteric vasculature.…”
Section: Introductionmentioning
confidence: 99%
“…To date, the mechanism of action remains unknown. Among others, voltage‐operated Ca 2+ channels were discussed as potential targets of PZQ ( 9 ), and recently also a (human) serotoninergic 5‐HT 2B receptor . After treatment, muscle contractions of the parasite are observed first before the worms are swept into the liver and are eliminated by inflammatory reactions .…”
Section: Anthelmintic Drug Therapymentioning
confidence: 99%